ФОРМУВАННЯ НАВЧАЛЬНОЇ МОТИВАЦІЇ МАЙБУТНІХ МАРКЕТОЛОГІВ У ПРОЦЕСІ ЇХ ПРОФЕСІЙНОЇ ПІДГОТОВКИ - Вершинська, Олена (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглянуто ефективність педагогічних умов формування професійної мотивації майбутніх маркетологів у процесі їх практичної підготовки; названо структурні компоненти професійної мотивації; визначено ієрархічну систему зовнішніх і внутрішніх мотивів навчальної діяльності студентів; проаналізовано рівень сформованості десяти типів мотивів навчальної діяльності за допомогою спеціально розробленого опитувальника; встановлено основні показники сформованості професійної мотивації студентів; узагальнено рівні усвідомленості, стабільності та дієвості професійної мотивації. В статье рассмотрено эффективность педагогических условий формирования профессиональной мотивации будущих маркетологов в процессе их практической подготовки; названо структурные компоненты профессиональной мотивации; определено иерархическую систему внешних и внутренних мотивов учебной деятельности студентов; проанализировано уровень сформированности десяти типов мотивов учебной деятельности с помощью специально разработанного опросника; установлено основные показатели сформированности профессиональной мотивации студентов; обобщено уровни осознанности, стабильности и действенности профессиональной мотивации. In the article efficiency of pedagogical terms of forming of professional motivation of future marketing specialists is considered in the process of their practical preparation; the structural components of professional motivation are adopted; on results psychological and pedagogical researches the structure of reasons that provide successful educational activity of students is distinguished; the hierarchical system of external and internal reasons of educational activity of students is certain; the level of formed of ten types of reasons of educational activity is analyzed by means of the specially worked out questionnaire; the basic indexes of formed of professional motivation of students are set; the levels of professional motivation are distinguished and it is set by means of the conducted questionnaire, that to the polled students inherent four types of professional motivation; generalized levels of realized, stability and effectiveness of professional motivation.